Students’ Satisfaction on Library Services at Faculty of Economics, Semarang State University - Undari, Diyah; Ismiyati, Ismiyati (Dinamika Pendidikan, 2015)
This research aims to know the factors that determine the students’ satisfaction and to know the most dominant factor in determining their satisfaction of the library‘s services at the Economics Faculty, Semarang State University.The data were collected by using questionnaire, documentation, and interview and then the data were analyzed by using factor analysis and descriptive percentage. Findings showe that 28 analyzed variables are reduced to 23 variables. They are grouped into eight new factors that determined the students’ satisfaction of 62.668%. Meanwhile, 37.332% are influenced by other factors that are not defined in this model. The convenience and the main products factor is17.971%, the interaction factor is 8.878%, the cleanliness factor is 7.830%, the neatness factor is 6.731%, the means of support factor is 6.348%, the technical performance factor is 5.597%, the building area factor is 4.918% and the complementary product factor is 4.396%.